IoT-Based Smart Energy Management System for Air-Conditioning Energy Efficiency in Mosques - Syaiful Amri; Rahmat Fajrul; Johny Custer; Murdani; Azizul (Program Studi Teknik Komputer, 2026)
Purpose – This study aims to develop and evaluate an Internet of Things (IoT)-based Smart Energy Management System (SEMS) to improve air-conditioning energy efficiency in mosque buildings. Design/methods/approach – The proposed system utilizes an infrared (IR) transmitter to replicate native air-conditioner remote signals, allowing implementation without modifying existing electrical installations. The system was implemented and tested at Taj-Al’ulum Mosque, Politeknik Negeri Bengkalis, under four operating modes: Default Manual, IoT Manual, Automatic, and Hybrid. Performance evaluation was conducted by comparing energy consumption across these modes and validating results through simulation and field testing. Findings – The results indicate that the Automatic mode achieved the highest energy savings, reducing energy consumption by 23.7% compared to the baseline, while also demonstrating the most stable operational performance. The Hybrid and IoT Manual modes also contributed to energy savings, although their effectiveness was influenced by user intervention and variations in mosque activities. Model validation showed strong agreement between simulation and real-world implementation, confirming system reliability. Research implications/limitations – This study is limited to a single case study location and focuses primarily on air-conditioning systems. Future research could expand to multiple buildings, integrate additional energy loads such as lighting and audio systems, and explore long-term performance under varying environmental and occupancy conditions. Originality/value – This study offers a practical, non-invasive, and replicable IoT-based energy management solution for mosque buildings, contributing to the development of smart energy management systems for smart mosques, particularly in environments with intermittent occupancy patterns.